PENGARUH KEPUASAN KERJA, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI DIVISI INDUSTRIAL DAN ENERGI PT HASKONING INDONESIA - Yumi Meirina (Universitas Mercu Buana, 2013)
Abstrack: The purpose of this study is to analyze the effect of job satisfaction, work environment and work motivation and its impact on the employee performance. The independent variable are job satisfaction, work environment and work motivation with employee performance as dependent variable. Primary data were collected by using questioner .Using total sampling, total 114 samples were obtained from employees inIndustrial and Energy Division PT Haskoning Indonesia. From the results of the data processing, the job satisfaction variables had no affect to the employee performance variable, work environment variable also had no affect to the employee performance variable, but work motivation affected to the employee performance variable. While job satisfaction, work environment and work motivation are simultaneously affect the performance of employees. The conclusionof this study, in order to affect employee performance, the company must increase employee motivation to obtain maximum results and meet the targets set.Keywords: job satisfaction, work environment, employee motivation, employee performance